Instagram Optimization as Hospital Digital Marketing Tool - Rahayu, Dina Nofitria; Anang Imam Massa Arif; Nikma Fitriasari (Jurnal Kedokteran Brawijaya, 2022)
Social media, one of which is Instagram, has been proven effective as a hospital marketing medium. A private hospital in Tulungagung Regency has had an Instagram account for four months but has not been well managed. As a result, the account does not function optimally and reflect digital marketing facilities. Based on this condition, the researchers aimed to analyze the ways to optimize Instagram as a hospital digital marketing tool. The method used was experimental research with pre- and post-experimental design without control in a private hospital in Tulungagung Regency in October 2021. The unit analyzed was the hospital marketing department. Two interventions were implemented, providing digital marketing training through Instagram and optimizing the hospital's Instagram management. The knowledge instrument was measured using a questionnaire, and the Instagram management instrument was measured by examining Instagram Insights. The results showed that Instagram training and management could optimize the use of Instagram as a hospital digital marketing tool. Knowledge about Instagram and activity increased after training and management on Instagram had been implemented. Yearly, monthly, and daily schedule preparation needs to be implemented to increase marketing optimization. The absence of a dedicated settle team in charge of managing the Instagram account makes the implementation challenging to evaluate. A team specifically addressing hospital social media will be able to focus the work and improve the management, so digital marketing through social media can be optimized.